2004
DOI: 10.1007/s10198-003-0220-3
|View full text |Cite
|
Sign up to set email alerts
|

Costs of treatment of colorectal cancer in different settings in Germany

Abstract: The objective of this study was to evaluate the cost implications of different settings (inpatient, outpatient/day clinic, or office-based oncologists) for the administration of standard fluoropyrimidine therapies, i.e., Mayo Clinic and Arbeitsgemeinschaft Internistische Onkologie (AIO)/Ardalan regimen, and to compare the results with the cost of oral capecitabine in Germany. In total, 89 quarterly fee-listings from 26 patients provided by 5 office-based oncologists were analyzed. Physician's services, drug co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…In particular, the major impact of the continuous 5-FU infusion costs has been established [9,15,24,28,32]. This 5-FU infusion cost has supported the favorable trends reported by recent economic studies for the use of raltitrexed, capecitabine, and tegafur [15,16,19,24,32]. To strengthen the base of future analyses it appears relevant to provide information about the distribution costs according to various schedules of continuous 5-FU infusion.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In particular, the major impact of the continuous 5-FU infusion costs has been established [9,15,24,28,32]. This 5-FU infusion cost has supported the favorable trends reported by recent economic studies for the use of raltitrexed, capecitabine, and tegafur [15,16,19,24,32]. To strengthen the base of future analyses it appears relevant to provide information about the distribution costs according to various schedules of continuous 5-FU infusion.…”
Section: Discussionmentioning
confidence: 68%
“…To strengthen the base of future analyses it appears relevant to provide information about the distribution costs according to various schedules of continuous 5-FU infusion. Several analyses have studied the costs related to conventional infusional 5-FU schedules [15,16,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier controlled studies have shown that patients who are randomized to adjuvant chemotherapy usually receive less than 80% of the calculated dosage [11,12]. We addressed this issue by performing a sensitivity analysis that assumed regimen-specific dose reductions as published in the literature.…”
Section: Results Of Sensitivity Analysesmentioning
confidence: 99%
“…The methods which are used by the Federal Statistical Office to calculate the health care expenditures are associated with some uncertainties (see methods of the cost of illness accounts of the Federal Statistical Office), but other German CRC cost studies are rare and the transferability of foreign calculations into the German setting is also not thoroughly recommendable [10][11][12]. There is a need for current, detailed CRC cost studies for the German setting to explore the economic burden of the disease as well as cost-driving parameters.…”
Section: Expenditurementioning
confidence: 99%